Impact of climate projections on Intensity-Duration-Frequency relationships of heavy rainfall in Pelotas/RS - Oliveira, Eduardo Peixoto de (2023)
One of climate changes (CC) main impacts are the projected increases in intensity and frequency of occurence of extreme hidrologyc events. Currently, the characterization of intense precipitaion patterns is given by the Intensity-Duration-Frequency (IDF) relation using observed data, however, in order to develop resilient infrastructure and reduce the risk of hydraulic structures’ failure in the future the use of climate projections is strategic in order to adress adaptation and mitigation measures on a local scale. It is presented a methodology for the adjustment of IDF curves for Pelotas/RS through the platform Genetic Algorithm Methodology for IDF (GAM-IDF) in order to compare the expected changes for events with 5 and 100 years of Return Period (RP) under the perspective of CC. Future projections for maximum anual precipitaion in 1 day generated by 4 global climate models downscaled by the regional climate model Eta under two Representative concentration pathways – RCP 4.5 and 8.5 until the end of the century (2006-2099) as well as daily pretipitation observed data (1966-2005) representative of the present are analysed. An increase in precipitation intensity is suggested on both RPs studied, specially on scenario RCP 4.5 and events of shorter duration, projecting averege increments of 11.5% and 25,6% for events with RP of 5 and 100 years, respectivelly, which may suggest an overload or even failure of future hydraulic structures that do not take CC into account during its design.